The Implementation of Parenting in Fostering Early Childhood Independence in Ngedukelu Village: Pelaksanaan Parenting dalam Membentuk Kemandirian Anak Usia Dini di Kelurahan Ngedukelu - Apolonia Bela; Efrida Ita; Elisabeth Tantiana Ngura; Konstantinus Dua Dhiu (Bestari: Jurnal Pendidikan dan Kebudayaan, 2026)
The purpose of this study was to determine how parents treat their early childhood children and the role of parents in building children's independence in Ngedukelu Village. This study aims to determine children's independence and how good parenting teaches children to perform simple tasks independently. This study focuses more on how parents educate children so that they can build their own independence. The results of the study indicate that children have not yet reached the expected level of independence. This condition is indicated by the fact that children still require parental assistance and guidance to carry out daily activities at home. Some activities that still require assistance include eating, putting on shoes, cleaning learning tools, and washing play equipment after use. Qualitative descriptive research was used. Case studies are the method used in this case. This study uses observation, interviews, and documentation to collect data. Data analysis includes data reduction, data provision, and drawing conclusions. The subjects of this study were children aged 4 to 6 years old, along with their parents. The data processing and analysis methods used in this study.